2007
DOI: 10.1021/ic060575i
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide-Bridged Mn(III)−Fe(III) Bimetallic Complexes Based on the Pentacyano(1-methylimidazole)ferrate(III) Building Block:  Structure and Magnetic Characterizations

Abstract: Seven cyanide-bridged bimetallic complexes have been synthesized by the reaction of [Fe(1-CH3im)(CN)5]2- with Mn(III) Schiff base complexes. Their crystal structure and magnetic properties have been characterized. Five complexes, [Mn2(5-Brsalen)2Fe(CN)5(1-CH3im)] x H2O (1), [Mn2(5-Clsalen)2(H2O)2Fe(CN)5(1-CH3im)] x H2O (2), [Mn2(5-Clsaltn)2(H2O)2Fe(CN)5(1-CH3im)] (3), [Mn2(5-Clsaltmen)2(H2O)2Fe(CN)5(1-CH3im)] x H2O (4), and [Mn2(5-Brsaltmen)2(H2O)2Fe(CN)5(1-CH3im)] x CH3OH (5), are neutral and trinuclear with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 92 publications
2
30
0
Order By: Relevance
“…Moreover, the magnetization values blow 10 kOe are low, further proving the presence of intermolecular magnetic interaction. Similar situations occur to other Mn(III)-containing high-spin polynuclear compounds [15]. DFT calculations and the experimental observations have shown that end-on doubly azide-bridged symmetric Cu 2 dimer should exhibit ferromagnetic coupling with Cu-N-Cu bond angles below 104°and antiferomagnetic larger than 104° [13].…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, the magnetization values blow 10 kOe are low, further proving the presence of intermolecular magnetic interaction. Similar situations occur to other Mn(III)-containing high-spin polynuclear compounds [15]. DFT calculations and the experimental observations have shown that end-on doubly azide-bridged symmetric Cu 2 dimer should exhibit ferromagnetic coupling with Cu-N-Cu bond angles below 104°and antiferomagnetic larger than 104° [13].…”
supporting
confidence: 64%
“…DFT calculations and the experimental observations have shown that end-on doubly azide-bridged symmetric Cu 2 dimer should exhibit ferromagnetic coupling with Cu-N-Cu bond angles below 104°and antiferomagnetic larger than 104° [13]. The bridging Cu-N-Cu bond angle of 102.68 (15)°in complex 1 lies below 104°, and thus ferromagnetic CuÁ Á ÁCu coupling is anticipated. The J CuCu value is comparable to that of complexes with similar Cu 2 (l 1,1 -N 3 ) 2 structural motif [11b,14].…”
mentioning
confidence: 97%
“…The presence of the tunneling relaxation readily explained the reduction of the energy barrier from Δ = |D ST |(S 2 T − 1/4) = 17.4 cm −1 (theoretical value) to 9.7 cm −1 (observed value). [116]. In all these compounds, [Mn III (SB)] + is capped by a water molecule forming discrete structures.…”
Section: Oligomers Including Single-molecule Magnetsmentioning
confidence: 99%
“…This symmetrical pentanuclear unit interacts with four neighboring units by forming an out-of-plane dimeric moiety in the [Mn III (saltmen)] + moieties as shown in Section 4, consequently constructing a 2D network having a dodecanuclear [ Mn III (O Ph ) 2 Mn III NC Fe III CN ] 4 cyclic repeat unit. Therefore, the Mn(III) ion has a distorted square bipyramidal geometry, in which the two apical sites are occupied by the nitrogen atom from [Fe III (CN) 6 [116]. The dc magnetic measurements displayed similar magnetic properties (J = 2.34(7) cm −1 , g = 2.04(2), zJ = 0.036(4) cm −1 ) exhibiting a long-range order at T c = 4.8 K.…”
Section: Two-dimensional Network Studiesmentioning
confidence: 99%
See 1 more Smart Citation